Meristem genes are essential for the vegetative reproduction of Kalanchoë pinnata - Jácome-Blásquez, Francisco; Kim, Minsung (Frontiers in Plant Science, 2023)
Several Kalanchoë species reproduce asexually by forming plantlets in the leaf crenulations. Some species produce plantlets incessantly via somatic embryogenesis and organogenesis, whereas others exclusively develop plantlets after leaf detachment, presumably through organogenesis. SHOOT MERISTEMLESS (STM), which mediates SAM functions, appears to be involved in Kalanchoë plantlet formation, suggesting that meristem genes may be essential for plantlet formation. However, the genetic regulatory network for establishing and maintaining plantlet primordia in Kalanchoë remains elusive. Here, we showed that meristem genes were differentially expressed in the leaf crenulations of K. pinnata during plantlet development after leaf detachment. The regulatory interactions among these meristem genes are largely conserved in K. pinnata crenulations. Moreover, transgenic antisense (AS) plants with lower expression of these key meristem genes formed significantly fewer plantlets with some morphological defects, suggesting that the meristem genes play an important role in plantlet formation and development. Our research revealed that key meristem genetic pathways were co-opted to the leaf margin to facilitate the unique asexual reproduction mechanism in K. pinnata. This also highlights how evolutionary tinkering invents new structures such as epiphyllous buds and plantlets by rewiring pre-existing genetic pathways.